Evaluation and assessment of cyber security based on Niagara framework: a review. Issue 3 (3rd July 2019) - Albettar, Maher
ABSTRACT: This paper reviews typical threats and attack vectors leading to unauthorized access to industrial networks via the corporate information system and facilitating subsequent attacks against under Niagara framework structures. The framework uses the Java VM as a common runtime environment across various operating systems and hardware platforms and it is designed from the ground up to assume that there will never be any one 'standard' network protocol, distributed architecture, or fieldbus. Niagara's design center is to integrate with all networks and protocols, also is targeted for embedded systems capable of running a Java VM, designed to provide scalability to highly distributed systems, Niagara using an architecture centered around the concept of 'Component Oriented Development', Components provide a model used to normalize the data and features of heterogeneous protocols and networks so that they can be integrated. But this technology also created new vulnerabilities there are a lot of risks and threats that might be exposed to attack the systems that use the Niagara framework.